Depictions of Human Trafficking and Exploitation in Contemporary Africa Using Akachi Adimora Ezeigbo’s Trafficked and Apio Eunice Otuku’s Zura Maids - Ocan, Johnson; Okumu, Charles Nelson; Sekiwu, Denis (East African Journal of Arts and Social Sciences, 2022)
In 2020, the government of Uganda reported investigating 214 incidents of human trafficking involving 154 suspects; of these incidents, 118 were internal, 93 transnationals, and three unknowns. This was a decrease compared with investigating 252 incidents (19 internal and 222 transnational) in 2019. This article examines how human trafficking and exploitation impacts on young girls from developing countries using Akachi Dimora Ezeig’s novel; ‘Trafficked’ and Apio Eunice Otuku’s ‘Zura Maids’. Using content analysis, the study engages critical discourse of postcolonial tenets understand the creation of inferiority complex, identity crisis, and cultural erosion among the colonized. As a result of social justice principle of “otherness”, which is a binary opposition between “I/We” and “Them”, the study packages the problem neatly, but offers few solutions for Africa, whilst condemning human trafficking and exploitation as a heinous act on humanity.
Keywords: Human Trafficking; Depictions; Forced Labour; Exploitation; Contemporary Africa; Maids